2012
DOI: 10.1259/dmfr/31640433
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Hounsfield units using grey levels in cone beam CT: a clinical application

Abstract: Objective: To present a clinical study demonstrating a method to derive Hounsfield units from grey levels in cone beam CT (CBCT). Methods: An acrylic intraoral reference object with aluminium, outer bone equivalent material (cortical bone), inner bone equivalent material (trabecular bone), polymethlymethacrylate and water equivalent material was used. Patients were asked if they would be willing to have an acrylic bite plate with the reference object placed in their mouth during a routine CBCT scan. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 16 publications
4
92
0
5
Order By: Relevance
“…Thus, CBCT has been proposed as a diagnostic method for the determination of bone mineral density [10,11,18,[34][35][36] . Gray values obtained with CBCT are used in an analog way as the HU values for the determination of mineral density [16] and show a linear relationship with the attenuation coefficients of the materials [13,15] , HU values obtained with medical CT [11,12,37,38] , and density values from DEXA [14] . Despite the correlation between gray values obtained with MSCT and CBCT, errors are expected when CBCT images are used to define the density of scanned structures [39] because these images present with inconsistencies and arbitrariness of gray values [16,40] , especially when related to abrupt changes of density in the object [41,42] , X-ray beam hardening effect [39,43] , scattered radiation [43] and projection data discontinuity-related effect [16] , making the validity of the measurements obtained questionable (Table 1).…”
Section: Cone Beam Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, CBCT has been proposed as a diagnostic method for the determination of bone mineral density [10,11,18,[34][35][36] . Gray values obtained with CBCT are used in an analog way as the HU values for the determination of mineral density [16] and show a linear relationship with the attenuation coefficients of the materials [13,15] , HU values obtained with medical CT [11,12,37,38] , and density values from DEXA [14] . Despite the correlation between gray values obtained with MSCT and CBCT, errors are expected when CBCT images are used to define the density of scanned structures [39] because these images present with inconsistencies and arbitrariness of gray values [16,40] , especially when related to abrupt changes of density in the object [41,42] , X-ray beam hardening effect [39,43] , scattered radiation [43] and projection data discontinuity-related effect [16] , making the validity of the measurements obtained questionable (Table 1).…”
Section: Cone Beam Ctmentioning
confidence: 99%
“…Once these artifacts exhibit a different color from that of the structure to be analyzed, they are responsible for the inconsistencies in the gray values in the areas where they are present [15,41,42] . Another source of artifacts in CBCT images is the phenomenon of X-ray beam hardening.…”
Section: Cone Beam Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between HU obtained from original attenuation coefficients (actual HU) with those calculated was very small and depended on the manufacturer of CBCT scanner and conditions in which the scan was taken. In vivo study conducted by the same authors showed the difference between the calculated and actual HU less than 3%, whereas the relationship between grey levels (voxel values) and HU was defined as linear [14]. It should be noted that the authors used a mathematical model only, without comparing CT and CBCT scans.…”
mentioning
confidence: 99%
“…The gray-scale CBCT values of the hypodense portion of the mass were measured. Using the gray-─ 68 ─ Arrested pneumatization of the sphenoid sinus mimicking intraosseous lesions of the skull base Inferior concha Choana scale values of the dental CBCT, Hounsfield units were derived using the comprehensive method described in the studies performed by Mah et al 11 and Reeves et al 12 The corrected Hounsfield units in the CBCT acquisition were characteristic of fatty tissue, suggesting the presence of fat surrounding the central, scattered curvilinear calcifications. The margins of the lesion were sharp and sclerotic, suggesting non-aggressive growth.…”
Section: Case Reportmentioning
confidence: 99%